(untitled) (Herald of Journalism, 2018)
The article deals with PR-technologies in building the reputation of the organization and functions, types. Currently, many companies use PR-technologies in shaping the organization’s reputation. Barnaul researcher M.B Gundarin indicates «Reputation – is a set of beliefs and a sense that the organization is in the audience for the formation of positive reputation: firstly to constantly maintain a lively dialogue with consumer groups; secondly seek to support a broad information openness;third to manage the reputation of systematically and continuously. Key words: PR, organization, reputation, audience M.B. Gundarin, group, type, technology, information.